Testing Methods Validation of Copper in Bottled Drinking Water Using Flame Atomic Absorption Spectrophotometry - Sa'adah Eva; Ari Surya Winata (Balai Riset dan Standardisasi Industri Pontianak, 2010)
Testing Laboratories of Institute for Industrial Research and Standardization (IIRS) Pontianak has used modified SNI 01-3554-2006 clause 2.22.2.1 in the testing of copper in bottled drinking water. Modification of the methods required validation. Validation aims to evaluate the suitability of such methods by means of laboratory study as standard testing methods in Various Commodity Testing Laboratory of IIRS Pontianak. Validation parameter conducted namely accuracy, precision, recovery, linearity methods, method detection limit, quantization limit, sensitivity, and measurement uncertainty. Based on the results of the validation methods and statistical data processing it was concluded that copper testing method in bottled drinking water using Flame Atomic Absorption Spectrophotometry (AAS) was compliant and suitable for use as standard testing methods in Various Commodity Testing Laboratory of IIRS Pontianak, indicated with good value of accuracy and precision, recovery 102.61%, method linearity correlation coefficient 0.9997, LOD 0.001 mg / L, LOQ 0.002 mg / L, sensitivity 0.0002 and uncertainty 0.0134 mg / L.